Investigating Students’ Perceptions on the Effectiveness of Entrepreneurship Education Module in Developing Students’ Entrepreneurial Competencies - Sirwan Ahmed Qader; Bakhtiar Kakil Hamad (Zanco Journal of Humanity Sciences)
Entrepreneurship is an important module to be incorporated into the higher education curriculum either as an independent module or integrally through other subjects. College of Basic Education, as an academic institution, took the initiative of adding EE indecently to its curriculum in 2016-2017. The purpose of adding it were to develop the students’ entrepreneurial competencies and graduate students that meet market demand.